Lesion Characterization by 99mTc-MIBI Myocardial Perfusion Imaging (MPI) & 18F-FDG Cardiac PET Following Myocardial Infarction Before Revascularization & Outcome Prediction: Initial Experience in Bangladesh (Journal of Invasive and Clinical Cardiology, 2024)
99mTc-MIBI SPECT myocardial perfusion imaging (MPI) and 18F-FDG cardiac positron emission tomography (Cardiac PET) can assess the extent and severity of myocardial perfusion and metabolic defect following myocardial infarction (MI) and also able to predict the outcome before revascularization in known coronary artery disease patients.  About 135 cases of known coronary artery disease patients were enrolled here for combined nuclear imaging tests, rest only ECG gated MPI and FDG cardiac PET to assess myocardial perfusion and viability status following MI prior to revascularization. In this study we want to figure out the utility of this combined protocol for myocardial lesion characterization and its role for clinical decision-making in-patient selection prior to revascularization and treatment planning. We are also intended to share the initial outcome in available follow up cases.J Inv Clin Cardiol 2023; 5(2): 45-52